Implementasi Pembelajaran Pendidikan Agama Islam Berbasis Multikulturalisme di Sekolah dengan Siswa Latar Belakang Beragam: Studi Kasus di SMP Muhammadiyah 08 Medan - Ananda, Miftah Rizki; Qorib, Muhammad; Zuliana, Zuliana (EduInovasi: Journal of Basic Educational Studies, 2025)
This research focuses on analyzing the implementation of Islamic Religious Education (PAI) learning at SMP Muhammadiyah 08 Medan. It aims to examine the extent to which multicultural values ​​are applied in the learning process for students from diverse backgrounds. This study uses a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation. The research findings demonstrate that PAI teachers are able to integrate multicultural values ​​into learning through interactive strategies linked to the realities of students' daily lives.